Association Between HIV and Prevalence and Manifestations of Asthma: Analysis of the Multicenter AIDS Cohort Study and Women's Interagency HIV Study. (15th December 2022) - Drummond, M. Bradley; Edmonds, Andrew; Ramirez, Catalina; Stosor, Valentina; Barjaktarevic, Igor Z.; Morris, Alison; McCormack, Meredith C.; Bhatt, Surya P.; Alcaide, Maria L.; Cribbs, Sushma K.; D'Souza, Gypsyamber; Bhandari, Neha; et al.
Abstract : Background: The association between HIV and asthma prevalence and manifestations remains unclear, with few studies including women. Setting: A retrospective observational cohort study from the Multicenter AIDS Cohort Study and Women's Interagency HIV Study. Methods: Asthma was defined in 2 ways: (1) self-report and (2) robust criteria requiring all the following: lack of fixed airflow obstruction, presence of wheeze on the St. George's Respiratory Questionnaire (SGRQ), and report of asthma therapies. Estimates of asthma prevalence and asthma-related manifestations were compared by HIV serostatus. Results: A total of 1815 men and 2122 women were included. Asthma prevalence did not differ between people with HIV (PWH) and people without HIV regardless of definition: self-report (men, 12.0% vs. 11.2%; women, 24.3% vs. 27.5%) and robust criteria (men, 5.0% vs. 3.4%; women, 12.8% vs. 13.2%). Among men with asthma, worse respiratory symptom burden was reported among those with HIV, regardless of asthma definition. Among women with self-reported asthma, those with HIV had less respiratory symptom burden. Regardless of serostatus, women with robust-defined asthma had similar respiratory symptoms across SGRQ domains and similar frequencies of phlegm, shortness of breath, and wheezing. Conclusions: Among PWH and people without HIV, asthma prevalence was 2-fold to 3-fold higher using self-reported definition rather than robust definition. In men and women, HIV was not associated with increased asthma prevalence. In men, HIV was associated with more respiratory symptoms when asthma was self-reported; the relationship was attenuated with the robust criteria. Further studies are needed to explore asthma phenotypes among PWH.